Oleoylethanolamide as a New Therapeutic Strategy to Alleviate Doxorubicin-Induced Cardiotoxicity - Qin, Yeyu; Xie, Jing; Zheng, Ruihe; Li, Yuhang; Wang, Haixia (Frontiers in Pharmacology, 2022)
Doxorubicin (DOX) is one of the most common chemotherapeutic anti-cancer drugs. However, its clinical use is restricted by serious cardiotoxicity. Oleoylethanolamide (OEA), a structural congener of endocannabinoid anandamide, is the endogenous agonist of peroxisome proliferator activated-receptor α (PPARα) and transient receptor potential cation channel vanilloid-1 (TRPV1), and involved in many physiological processes. The present study aimed to determine whether OEA treatment protects against DOX-induced cytotoxicity (DIC) and gain insights into the underlying mechanism that mediate these effects. Our data revealed that OEA treatment improved the myocardial structure in DOX-challenged mice by attenuating cardiac oxidative stress and cell apoptosis. OEA also alleviated DOX-induced oxidative stress and apoptosis dysregulation in HL-1 cardiomyocyte. These effects were mediated by activation of TRPV1 and upregulation of PI3K/ Akt signaling pathway. Inhibition of TRPV1 and PI3K reversed the protective effects of OEA. Taken together, our data suggested that OEA protects against DIC through a TRPV1- mediated PI3K/ Akt pathway.